PENGARUH DISIPLIN BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI SMAN 13 MEDAN T.A 2025/2026 - Vailimlim Simamora; Charles Fransiscus Ambarita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the effect of learning discipline and learning independence on the economic learning achievement of 11th-grade students at SMAN 13 Medan in the 2025/2026 academic year. The study uses a quantitative approach with an ex-post facto method. The population of the study includes all 11th-grade students consisting of four classes, with a sample of 105 students selected using simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 26. The results of the study show the regression equation Y = 60.410 + 0.246X₁ + 0.174X₂ + e. Partially, learning discipline has a positive and significant effect on academic achievement with a t-count value = 5.995 > t-table = 1.659 and significance 0.000 < 0.05. Learning independence also has a positive and significant effect on academic achievement with a t-count value = 4.154 > t-table = 1.659 and significance 0.000 < 0.05. Simultaneously, learning discipline and independence. Simultaneously, study discipline and learning independence have a positive and significant effect on academic achievement, with a calculated F value of 125.185 > table F of 3.09 and a significance of 0.000 < 0.05. These two variables contribute 71.1% to academic achievement, while 28.9% is influenced by other factors outside the study. Thus, study discipline and learning independence positively and significantly affect the economics learning achievement of 11th grade students at SMAN 13 Medan